Exploration of sponge city construction in China from the perspective of typical cases - Shang, Shouwei; Wang, Leizhi; Wang, Yintang; Su, Xin; Li, Lingjie; Xia, Xiaohan (Frontiers in Earth Science, 2023)
Eight Night years have witnessed the construction of sponge cities city in China. In recent years, more frequent extreme rainstorm has put more pressure on urban flood control and waterlogging elimination, and the construction of sponge city has been facing many controversies. In response, this study discusses the concept, connotation, evaluation indexes, construction objectives, investment and benefits of sponge city construction. The key point is that the concept of the sponge city has expanded from the construction of low-impact development to a new model of urban development and construction, with an emphasis on improving the overall function of the city and enhancing the comprehensive response to urban water issues. Its construction benefits cannot be measured only in terms of flood control and waterlogging prevention. Besides, the biggest problem faced by cities is still flooding. The priority of building a sponge city is the prevention of waterlogging. Meanwhile, the integrity and systematic construction which integrates multiple sectors, industries and fields should be considered. The government should focus on the combination of ecological methods and engineering facilities, and scientifically promote the systematic management of urban water.